Stock-flow consistent modeling through the ages - Eugenio Caverzasi; Antoine Godin (Levy Economics Institute of Bard College, 2013)
The aim of the paper is to provide an overview of the current stock-flow consistent (SFC) literature. Indeed, we feel the SFC approach has recently led to a blossoming literature, requiring a new summary after the work of Dos Santos (2006) and, above all, after the publication of the main reference work on the methodology, Godley and Lavoie's Monetary Economics: An Integrated Approach to Credit, Money, Income, Production and Wealth (2007). The paper is developed along the following lines. First, a brief historical analysis investigates the roots of this class of models that can be traced as far back as 1949 and the work of Copeland. Second, the competing points of view regarding some of its main controversial aspects are underlined and used to classify the different methodological approaches followed in using these models. Namely, we discuss (1) how the models are solved, (2) the treatment of time and its implication, and (3) the need-or not-of microfoundations. These results are then used in the third section of the paper to develop a bifocal perspective, which allows us to divide the literature reviewed according to both its subject and the methodology. We explore various topics such as financialization, exchange rate modeling, policy implication, the need for a common framework within the post-Keynesian literature, and the empirical use of SFC models. Finally, the conclusions present some hypotheses (and wishes) over the possible lines of development of the stock-flow consistent models.
Keywords: B59; C69; E12; 330; stock-flow consistent; post-Keynesian; literature review